Thermoeconomic analysis of pvc production plant reactors cooling system (2017)
In this work the results of the research made to PVC production plant reactors cooling system are included. The heat generated in the reactor must be removed to maintain its temperature at an optimal range between 50 and 70 °C. To assess the cooling system exergetic and Thermoeconomic indicators were used and it was observed that: (i) The greatest exergetic efficiencies arise in compressors. (ii) The greatest destruction of exergy and reasons of destruction of exergy cost and lower exergoeconomic factors are presented in the evaporative condenser. (iii) The heat exchange equipment has highest relative cost differences. © 2018 ASME.